2009
DOI: 10.1007/s12302-009-0042-8
|View full text |Cite
|
Sign up to set email alerts
|

Schnecken unter Stress

Abstract: Zusammenfassung Hintergrund Schnecken sind in der ökotoxikologischen und ökophysiologischen Forschung als Zielorganismen für Molluskizide ebenso wie als Nicht-Zielorganismen für Umweltchemikalien und andere Umweltstressoren von Bedeutung. In beiden Fällen werden Biomarker auf verschiedenen biologischen Ebenen untersucht, um zu verstehen, welche Mechanismen die Tiere dazu befähi-gen, ungünstige Lebensbedingungen zu bewältigen oder gar für sich zu nutzen. Schwerpunkte Der Schwerpunkt des Artikels liegt auf der E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 65 publications
(27 reference statements)
0
2
0
Order By: Relevance
“…Cortet et al, 1999). Various studies have been performed assessing the effects of different heavy metals on growth, food consumption, fecundity, mortality and molecular stress responses in terrestrial molluscs, mainly snails (Cortet et al, 1999;Triebskorn, 2009;De Vaufleury, 2015). For the retrospective risk assessment of metals, a standard test is requested to assess the soil quality using the vineyard snail Helix aspersa M € uller (ISO, 2006).…”
Section: Eisenia Fetida Compared With Gastropodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cortet et al, 1999). Various studies have been performed assessing the effects of different heavy metals on growth, food consumption, fecundity, mortality and molecular stress responses in terrestrial molluscs, mainly snails (Cortet et al, 1999;Triebskorn, 2009;De Vaufleury, 2015). For the retrospective risk assessment of metals, a standard test is requested to assess the soil quality using the vineyard snail Helix aspersa M € uller (ISO, 2006).…”
Section: Eisenia Fetida Compared With Gastropodsmentioning
confidence: 99%
“…In the guideline, a test procedure to assess the effect of exposure to contaminated soil and a procedure to assess the effect of contaminated food mainly on growth (but also lethality) of juveniles of H. aspersa are described. This test is well qualified to assess the effect of metal contamination (Triebskorn, 2009) but as emphasised in the guideline itself, the test is not adequate to test volatile compounds. (Sverdrup et al, 2006) showed that it is not very suitable to assess the effects of PAHs.…”
Section: Eisenia Fetida Compared With Gastropodsmentioning
confidence: 99%